Taxation in Brazil in the Napoleonic Wars: neutrality, economy and the outcomes of a royal court in transit - Dominguez, Rodrigo da Costa (2019)
Over the last three decades, Brazilian historiography has testified the growing and development of Economic History studies. Regardless of chronology, topics, original databases and new methodologies utilized, its recent “boom” carries out the great influence of classic and traditional approaches, as well as the latest contribution of native scholars, especially concerning relevant themes such as economic growth and policies, dependence and development during the nineteenth and twentieth centuries, different forms of credit, banking history, economic activities and so on. Conventional methods and data have been recently challenged by innovative perspectives regarding the sources previously known by economic historians, as well as some new data brought up by this new generation’s work. In this recent historiographical scenario, colonial economic aspects have been privileged, with trade and taxation occupying a prominent place. In this chapter, the authors’ goals are to bring out a Brazilian historiographic panorama that has influenced these “new” economic history schools of thought, as well as to summarize some important economic studies recently developed during this period regarding these topics. Moreover, it aims to outline the impact of opening Brazilian ports in 1808, with regard to Brazilian economic growth so far and the contrast between the Alfandegas (customs) movement in Brazil (Rio de Janeiro) and Portugal (Lisbon), in order to verify the paradigm shift which meant (in terms of revenues and taxation) the transfer of the Portuguese court to Brazil within the context of the Napoleonic Wars.